2019
DOI: 10.1111/1748-5967.12387
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence rates of wild rodent hosts and chigger mites and the infection rate ofOrientia tsutsugamushiin the central region of South Korea from 2015 to 2018

Abstract: Outbreaks of vector‐borne diseases are dramatically increasing because of climate change, consequently increasing the importance of surveillance of endemic disease vectors. In this study, we surveyed chigger mites, vectors for Orientia tsutsugamushi—the bacteria that causes Tsutsugamushi disease—, and their rodent hosts in Gimcheon, central South Korea, in 2015–2018. A total of 225 rodents were collected, with trap rate and percentage of rodents infected by chigger mites of 9.8 and 72.4%, respectively. Six spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…In this study, many samples were collected in spring and autumn, and only a few were collected in summer. This finding is consistent with the fact that chigger mites occur frequently in spring and autumn, and rarely in summer (Choi et al 2019) (Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, many samples were collected in spring and autumn, and only a few were collected in summer. This finding is consistent with the fact that chigger mites occur frequently in spring and autumn, and rarely in summer (Choi et al 2019) (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, according to Song (2016) and Choi et al (2019), A. agrarius was the most common species of wild rodent in South Korea, with a proportion of above 80%. In addition, Song (2016), Park et al (2018), Choi et al (2019) showed that the total trapping rate (TR) of wild rodents was 7.6 to 13.6, which was 0.52. This different may be caused by the differences in the environment and geographical conditions of the survey areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations